2006
DOI: 10.1143/jjap.45.3592
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Epitaxial Si Films Grown by Atmospheric Pressure Plasma Chemical Vapor Deposition Using Cylindrical Rotary Electrode

Abstract: Epitaxial Si films have been grown at low temperatures (500 -700 C) by atmospheric pressure plasma chemical vapor deposition using a cylindrical rotary electrode. The variation in Si film quality across the entire deposition area has been investigated. It is found that defect-free epitaxial Si growth is possible at 500 C with sufficient plasma power in the central part of the film. At film edges, however, there are narrow regions of polycrystalline growth. From the deposition experiments under simplified bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…From these experimental findings, we believe that an intense reaction at the central part of the high-density AP hydrogen plasma forms a large amount of SiH x products and that they will decompose within the plasma downstream to form poly-Si films on the SiC surface. Considering that a high-quality epitaxial Si film is formed by AP-PCVD technique, 14 we believe that the plasma-induced damage can be neglected and that the amorphous layer remained at the central portion is attributed to the quenched surface with SiC x H y products.…”
Section: High-speed Etching Using Cylindrical Rotary Electrodementioning
confidence: 99%
See 1 more Smart Citation
“…From these experimental findings, we believe that an intense reaction at the central part of the high-density AP hydrogen plasma forms a large amount of SiH x products and that they will decompose within the plasma downstream to form poly-Si films on the SiC surface. Considering that a high-quality epitaxial Si film is formed by AP-PCVD technique, 14 we believe that the plasma-induced damage can be neglected and that the amorphous layer remained at the central portion is attributed to the quenched surface with SiC x H y products.…”
Section: High-speed Etching Using Cylindrical Rotary Electrodementioning
confidence: 99%
“…Atmospheric pressure (AP) plasma has the advantage of generating high-density radical species, in which ion bombardment can be suppressed when using a 150-MHz very high-frequency (VHF) power supply. [13][14][15] Low-temperature growth of high-quality epitaxial Si films has been performed with the AP plasma chemical vapor deposition (PCVD) method using gas mixtures containing He, H 2 , and SiH 4 . In this study, aiming at damage-free and flat SiC surfaces under low process temperatures, we propose a novel and efficient surface cleaning and etching method of SiC wafers using AP hydrogen plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the reduction of substrate heating temperature and the suppression of ion damage of the film are simultaneously expected by utilizing atmospheric pressure plasma. In contrast to the conventional PECVD technique, it is shown that AP-PCVD is a promising technique for the high-rate and low-temperature growth of high-quality functional thin films [4][5][6][7][8][9][10]. The aim of this study is to develop a new technology for the formation of gate oxide layers with good dielectric strength, low interface trap density and low fixed oxide charge density, utilizing the physical and chemical properties of atmospheric pressure plasma.…”
Section: Introductionmentioning
confidence: 99%
“…The RHEED image in the milky part shows a polycrystalline ring pattern. Although the central part of the Si film is a defect-free single crystal, 9,10) the growth of a high-quality epitaxial Si film on the entire wafer surface is impossible by scanning the substrate, Deposition time (min) 1. 5 4 -5 because the polycrystallization at the film edge on the upstream side affects the crystallinity of the deposited Si film.…”
Section: Characterization Of Si Films Grown Using Cylindricalmentioning
confidence: 99%